2002
DOI: 10.1177/154596802401105207
|View full text |Cite
|
Sign up to set email alerts
|

Hand Motor Recovery after Stroke: A Transcranial Magnetic Stimulation Mapping Study of Motor Output Areas and Their Relation to Functional Status

Abstract: The respective contributions of the stroke and undamaged hemispheres to motor recovery after stroke remains controversial. The aim of this article is to evaluate the relationship between location and size of cortical motor areas and outcome after stroke. Twelve controls and 12 stroke patients were studied. Hand cortical motor output areas were determined using transcranial magnetic stimulation. Motor-evoked potentials were recorded simultaneouslyfrom both hands. Functional motor abilities were evaluated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 29 publications
1
21
3
Order By: Relevance
“…This is consistent with animal studies that demonstrated expansion of neural elements in the non-injured hemisphere in animals recovering from a unilateral lesion [44,45]. Although when compared to control subjects, Transcranial Magnetic Stimulation (TMS) parameters (such as lower motor threshold, easier to obtain ipsilateral motor evoked potentialsMEPs, reduced intra-cortical inhibition) [46] point to increased cortical excitability in the contralesional sensorimotor cortex (SMC) following stroke, this is not essentially associated with good recovery [35,47,48]. It is the development of contralateral MEPs by stimulation of the affected hemisphere that heralds return of function in the hand [49].…”
Section: Discussionsupporting
confidence: 72%
“…This is consistent with animal studies that demonstrated expansion of neural elements in the non-injured hemisphere in animals recovering from a unilateral lesion [44,45]. Although when compared to control subjects, Transcranial Magnetic Stimulation (TMS) parameters (such as lower motor threshold, easier to obtain ipsilateral motor evoked potentialsMEPs, reduced intra-cortical inhibition) [46] point to increased cortical excitability in the contralesional sensorimotor cortex (SMC) following stroke, this is not essentially associated with good recovery [35,47,48]. It is the development of contralateral MEPs by stimulation of the affected hemisphere that heralds return of function in the hand [49].…”
Section: Discussionsupporting
confidence: 72%
“…A positive association between poststroke motor function and TMS activation area has also been reported in cross-sectional studies. 22 These longitudinal results indicate that TMS map-size enlargement signals at least one mechanism through which cerebral reorganization participates in motor recovery. Interpretation of map-size enlargement is problematic because changes in map size reflect alteration in motor cortical output excitability and can be explained by different mechanisms.…”
mentioning
confidence: 79%
“…Following this, the peak-to-peak amplitude and area of each MEP are identified and then averaged to determine the mean value of the individual trials (Carroll et al, 2001;Kiers et al, 1993;Magistris et al, 1998;Miranda et al, 1997;Ridding and Rothwell, 1997). Alternatively, an ensemble averaged MEP can be generated and the peak-to-peak amplitude and area of this waveform then determined (Bastings et al, 2002;Pitcher and Miles, 2002;Pitcher et al, 2003). Less commonly, the largest MEP at a set stimulus intensity is identified and the peak-to-peak amplitude of this response is used (Eisen et al, 1991).…”
Section: Introductionmentioning
confidence: 99%